Tanggung Jawab Notaris Terhadap Akta Hak Waris Yang Mengalami Degradasi Nilai Pembuktian (Studi Putusan PN Cianjur No. 259/PID.B/2015/PN.CJR) - Salman Abror; Adi Mansar; Ferry Susanto Limbong (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This paper aims to analyze and find answers to the problem of the notary's responsibility for the inheritance rights deed which has degraded the evidentiary value by studying the decision of the Cianjur District Court No. 259/PID.B/2015/PN.CJR. The problem is focused on how the notary's responsibility is in the case of the deed of inheritance rights which has degraded the value of the proof due to a court decision that has permanent legal force and how the legal protection for the parties contained in the deed of inheritance rights has experienced a degradation of evidentiary value due to a court decision that has a force permanent law. In order to approach this problem, a normative legal research type that is descriptive analytical is used by using secondary data as the main data and primary data as complementary data. This research uses data collection techniques with library studies and qualitative data analysis. This study concludes that the notary is responsible for the deed of inheritance rights which has deglazed the value of proof based on the moral code of ethics and responsibility based on state law. Liability is determined based on the nature of the violation and the resulting legal consequences, accountability can be in the form of administrative sanctions and civil sanctions. Legal protection can be obtained through civil action and through the local notary supervisory agency and the notary can then report the notary to the Regional Supervisory Council.